Simulation of Crowd Movement during Pandemic Covid-19 - Zakariya, Ummu Zahratul Farihah; Mohamad, Shamsul; Rafizah Mohd Hanifa (Evolution in Electrical and Electronic Engineering, 2022)
During the COVID-19 outbreak, new norms were taught in the community, such as the need for the social distancing of each people in daily life. Using computer software, we can produce simulations that can show the movement of people in a particular space that considers social distancing. This simulation can help plan people's movement during the covid-19 pandemic with a social distance of 1 meter. Agents and layouts of surau, hall and supermarket were modelled using Microsoft Visual Studio. The Social Force Model (SFM) was used to produce simulations of crowd movement. SFM describes the motion of an agent as a combination of the driving force, the repulsive force of another agent and the repulsive force of an object. This simulation shows the time and a maximum number of agents that can be in a space considered with social distancing. In addition, the simulation results also show the average time taken by the agents to fill up some spaces and consider the time taken by some agents to make close contact with each other.